Pulse consumption trends in the US in the context of 2025–30 Dietary Guidelines for Americans: analyses of NHANES data for 1999–2018 - Drewnowski, Adam; Zavela, Catherine; Tran, Vanessa; Mallya, Greeshma; Conrad, Zach (Frontiers in Nutrition, 2025)
BackgroundThe 2025–30 US Dietary Guidelines Advisory Committee has recommended moving pulses to the Protein Foods Group and listing them ahead of meat, poultry, and eggs. The recommended amounts went up from 1.5 to 2.5 cups/week per 2,000 kcal daily.ObjectiveTo track temporal trends in pulse consumption in the US from 1999 to 2018 by consumer socio-demographics and by pulse type.MethodsDietary intakes data came from 10 cycles of the National Health and Nutrition Examination Survey (NHANES 1999–2018). Adult participants were stratified by sex, age group, income to poverty ratio (IPR), education, and race/ethnicity Pulses were separated into beans, chickpeas, peas, and lentils. Analyses were conducted for the whole sample (n = 48,738) and for pulse consumers (n = 9,186). Trend analyses were based on linear regression models.ResultsAcross all years tested, only 17.2% of NHANES participants consumed any pulses on a given day. Mean prevalence was highest among Mexican Americans (33.3%) and lowest among non-Hispanic Black groups (12.0%). Consumption prevalence dropped after 1999–2000 but recovered after 2007–08. Mean consumption of cooked pulses was 0.39 oz/day overall and 2.26 oz/day among consumers. Higher amounts were consumed by Mexican Americans, men, and groups with lower education and incomes. In 2017–2018, 19.9% of the population consumed 1.5 cups/week of cooked pulses and 10.9% consumed 2.5 cups/week. Beans were the most consumed pulse followed by lentils, chickpeas, and peas. Unlike beans, both lentils and chickpeas were associated with higher socioeconomic status.ConclusionOther than among Mexican Americans, pulse consumption in the US was low and was associated with lower education and incomes. However, pulse consumers consumed substantial amounts. Lentils and chickpeas may represent opportunities for increasing pulse consumption. The present findings are relevant to the implementation of the 2025–30 Dietary Guidelines for Americans and can help target the promotion of pulses among population subgroups.